Զավեն Մահտեսի Բաբայան (1876-1925) - Բաբայան, Օֆելյա (ԱրՊՀ հրատ․)
Исполнилось 140-летие священнослужителя родом из Арцаха Завена Магтеси Бабаяна. В 1911-1916гг, он работал временным правителем Карабахской епархии. В те годы, 1913г., отмечалось 75-летие Карабахской армянской епархической школы, в Арцахе восстановилась армянская периодическая печать, в ноябре 1911г. Стала издаваться газета “Карабах”. В мае 1918г., будучи руководителем епархии Эрзрума, он и Гарегин Овсепян, высоко держа крест в руках, в битве Сардарапата шли впереди полка смертников к осознанной смерти. Завен Магтеси Бабаян родился в селе Гиши, был монахом, епископом, похоронен во дворе церкви с. Гаяне Эчмиацина, по соседству с героями Сардарапата. It has been celebrated the 140 anniversary of ZavenMahtesiBabayan. In 1911-1916 he was the temporal head of karabkhian diocese. In 1913, the 75-years of karabkhian Armenian diocesan school was celebrated under his leadership and the periodical press of Artsakh was reformed. The journal <<Karabakh>> (1911, November) was published in Shushi. In May 1918, being already the head of Erzrum diocese, ZavenBabayan together with GаreginHovsepyan holding the cross high in hand, was going to his doom in the battle of Sardarabad. ZavenMahtesiBabayan was born in the village of Gishi. He was a monk, bishop and is buried in the yard of St. Gayane's Church, Etchmiadzin, in the neighbourhood of Sardarabad heroes.
Keywords: Հայ եկեղեցու գործիչներ